Experimental acute Clostridium perfringens type D enterotoxemia in sheep is not characterized by specific renal lesions. Issue 4 (July 2023) - Giannitti, Federico; García, Jorge P.; Adams, Vicki; Armendano, Joaquín I.; Beingesser, Juliann; Rood, Julian I.; Uzal, Francisco A.
Type D enterotoxemia, caused by Clostridium perfringens epsilon toxin (ETX), is one of the most economically important clostridial diseases of sheep. Acute type D enterotoxemia is characterized by well-documented lesions in the nervous, cardiocirculatory, and pulmonary systems. However, discrepancies and confusion exist as to whether renal lesions are part of the spectrum of lesions of this condition, which is controversial considering that for many decades it has been colloquially referred to as "pulpy kidney disease." Here, the authors assess renal changes in an experimental model of acute type D enterotoxemia in sheep and evaluate the possible role of ETX in their genesis. Four groups of 6 sheep each were intraduodenally inoculated with either a wild-type virulent C. perfringens type D strain, an etx knockout mutant unable to produce ETX, the etx mutant strain complemented with the wild-type etx gene that regains the ETX toxin production, or sterile culture medium (control group). All sheep were autopsied less than 24 hours after inoculation; none of them developed gross lesions in the kidneys. Ten predefined histologic renal changes were scored in each sheep. The proportion of sheep with microscopic changes and their severity scores did not differ significantly between groups. Mild intratubular medullary hemorrhage was observed in only 2 of the 12 sheep inoculated with the wild-type or etx -complemented bacterial strains, but not in the 12 sheep of the other 2 groups. The authors conclude that no specific gross or histologic renal lesions are observed in sheep with experimental acute type D enterotoxemia.